Efficiency And Effectiveness Performances Of Hydro-Powered Water Pump (Path) Technology Application - Novayanti, Nina; Saraswati, Erwin; Iqbal, Syaiful (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
This research aims to analyze the effectiveness and efficiency performance of the implementation of Hydro Water Pump technology in Wonokerso Village, Temanggung Regency. This research uses a qualitative method with a case study approach. Primary data was obtained through Focus Group Discussions and interviews with stakeholders, while secondary data was obtained from related documents. Effectiveness performance analysis was conducted using the Social Return on Investment method to measure the social, economic, and environmental impacts of PATH technology implementation, while efficiency performance was measured by comparing the outputs produced with the inputs used. The results showed that the effectiveness performance of PATH technology implementation in Wonokerso Village improved farmers' welfare by increasing the planting period from twice to three times a year, increasing the spirit of mutual cooperation and harmony among farmers and maintaining air cleanliness because it was able to provide irrigation water with non-oil fueled water pump technology. Thus, this program can be said to be effective so that it can be implemented further. Therefore, this study concludes that the application of PATH technology in Wonokerso Village is efficient and effective, so it can be implemented further.